Reflexões sobre o absurdo – o corpo-cabelo e seus objetos de (in)definição - Azevêdo, Anna Behatriz Alves de (2018)
The following dissertation aims to reflect on the body through the perspective of the relationship in which bodies are able to affect and be affected by the bias of perception and sensation which comprise the vibrating body. The methodological path of this research is divided into three chapters that contaminate each other and the chosen method is Cartography. It is to lead the discussions through text in which images, conversations and, especially the performance / program created by me in 2015 titled Abduction for small revolutions, are triggers for the development of essays that permeate report of experience and academic writing. The ideas of absurdity, the paradoxical latency of the living (tangles of life and death), relations of domination and submission, are part of the scope of the discussions, and hair, be it in the head or outside it, is the main element for triggering affairs. Together and through the images and conversations, I articulate reflections and self-reflections about and with such an element chained in experiences, both in the artistic production bias as in the daily life. In the first chapter I started with the image of a photograph of Ana (my mother), together and through conversations with her in everyday life, we come to the idea of ​​the Lost Braid which is the return to aspects of her history. This braid is a force that opens the door to questions about absences generated by naturalizations that actions and segregating discourses form in our bodies, such as those generated by symbolic violence, linked to the androcentric and phlogologocentric logics, The Lost Braid is a force that rubs image, conversation and written, in the midst of the narrated memories of picking nits and lice as activators of affections. In the second chapter Screaming Hooks, I work with the logic of sensation and the concept of "body-vibrating." In relationships created by the gestures of scratching and shaving the head, I also come to the experience of a vertiginous and reeling body that can be restored or not, such sensations are potentialized from the "affects of vitality." In addition, I outline situations and experiences about and with the hair and the maintenance of the shaved head, presenting some examples of images of women who had their hair shaved and reports of artists, mostly women, in which the hair element or the absence of it in the head is present in his works. Finally I enter the third chapter entitled Body-Hair in which the performance / program Abduction for small revolutions is field of study. I present this work to 12 people and I develop a dialogue with them about the event of the action and the elements (especially the hair and the absence of it in the head) and gestures that compose it. So to speak, I start from the assumption that the body in performance / artistic program is a body that acts in relation to other bodies. Since then, the performance / Abduction program for small revolutions is revealed from this encounter, thus creating perspectives around the absurd, the paradoxical latency of the living that can define a set of affections, which move the body from the place of mere instrument and artistic tool for the place of experience and re-existence.